Investigating Co, Cu, and Pb retention and remobilization after drying and rewetting treatments in greenhouse laboratory-scale constructed treatments with and without Typha angustifolia, and connected phytoremediation potential. (15th April 2019) - Nabuyanda, Misery Mulele; van Bruggen, Johan; Kelderman, Peter; Irvine, Kenneth
Abstract: There is critical concern over heavy metals because they are biotoxins. The best management option is elimination or at least minimization of effluence into the environment, but in several regions, mining wastewater or acid mine drainage (AMD) effluence into natural wetlands has continued. The ability of wetlands to attenuate heavy metals in mining wastewater and AMD has led to natural wetlands being used as recipients of these effluents in many parts of the world. Ten greenhouse-based laboratory-scale constructed wetlands (GLCW) were set up at IHE-Delft Institute for Water Education to understand the mechanisms and fate of heavy metals in three Zambian wetlands in attenuation of Co, Cu, and Pb. These were operated as Free Water Surface Constructed Wetlands (FWS-CWs). The principal investigations compared how vegetated and unvegetated microcosm artificial wetlands retained controlled additions of heavy metals and the effect of drying and rewetting on that. The potential for phytoremediation using Typha angustifolia was also investigated. Typha angustifolia was planted in three vegetated and compared with one unvegetated treatment. Treatments A, B, and, the investigated, Treatment D received synthetic wastewater containing Co, Cu, and Pb, while a control, Treatment C, received tap water. Water samples were taken throughout the experiment, and sediment samples collected after the first flushing and before drying. Samples of T. angustifolia were taken before drying the wetlands. Analyses for Co, Cu, and Pb were made in the water and sediment, and in roots, stems and leaves of plant samples. The unvegetated Dutch sediments GLCWs removed more Co from wastewater (52%) than the vegetated Dutch and Zambian sediments GLCWs (13% and −4%, respectively). There was a similar removal of Cu among the GLCWs receiving wastewater (81%–87%). The removal of Pb was significantly higher in the vegetated Dutch sediment GLCWs than the unvegetated Dutch sediments GLCWs, (89% and 72%, respectively). It was concluded that a hectare of the vegetated Zambian sediments with similar design parameters of 50 mg/m 2 .day for Co, Cu, and Pb used in the experiment would on average retain 83 g/day of Co, and 417 g/day of both Cu and Pb. After drying, Co, Cu, and Pb washed out on the first day of rewetting. The washout after that took only a few days. How long the metals washed out of the GLCWs was in order Co > Cu > Pb. T. angustifolia could neither be classified as an accumulator nor an excluder species because the concentrations of Co, Cu, and Pb in the sediments and T. angustifolia were below phytotoxic levels mainly due to a short running period of the experiment.